Infrastructural orphans: finding a new meaning and purpose for the 2010 World Cup stadia - the Peter Mokaba stadium case study - Van Niekerk, Stefan (My University, 2016)
Six years after the 2010 FIFA World Cup was hosted by South Africa many researchers are still contemplating the so-called positive spin-offs that was propagated (Bond & Cottle, 2012: 1) leading up to this mega-event. Massive capital over-spending, increased public debt and severe under utilisation of these newly constructed iconic stadia and surrounding infrastructure are reported which is representative of the sobering realisation that mega-events, contrary to popular belief, may not be the ‘begin all, end all’ catalyst for urban development – a critique that has been noted in many countries of the north (Haferburg, 2011: 334). Now that the sound of cheering crowds have faded along with visual images honouring the mega-event (Young, 2015), we are faced with the stark realisation that cities need to maintain these expensive facilities and actively seek to attract large events to ensure a relatively stable stream of much required revenue. Santos (2014) questions the amount of rationality applied when such investment decisions are made and points to the generally accepted and portrayed idea that these new iconic stadia will somehow translate into other socio-economic benefits, but argues that due to the rather inflexible use of these facilities, it is very seldom that positive spin-offs are actually realisable. Therefore public investment and expenditure decisions by government have a more significant impact on the inhabitants of an area as they themselves suffer the burden of budgetary deficits, severely increased public debt (Hoiris, 2012), and most importantly, the spatial and resulting socio-economic consequences of ill-advised development. This mammoth of a task (of maintaining facilities) is even further complicated by various degrees of local detachment, socially and functionally, and therefore interventions will need to seek alternative ways to facilitate a sort of ‘re-integration’ into the existing urban fabric by a process of land use redefinition and spatial reconfiguration. Such an issue and approach is no different to the Peter Makoba Stadium in Polokwane and therefore this research will utilise the site as a case study in an attempt to discover whether and how urban design can re-integrate such facilities into cities by developing a new image, use and meaning in order for it to more appropriately fit into the local context. The study firstly explored how and why mega-events has been utilised for urban development globally and what the collective experiences have been. A precedent study was then conducted to determine how other cities have dealt with these challenges and to what extent it has been deemed successful. A process of design approach formulation and interpretation was undertaken that ultimately influenced and informed the proposed urban design interventions for the Peter Makoba Sports Precinct. The proposed urban design interventions is however further aligned to the City of Polokwane’s long term development vision and therefore gives spatial expression to forward planning policies in a more coherent and systematic manner. Finally conclusions are drawn from the study that can serve as a guideline for the future design and development of such facilities. This study therefore explores how a new social and economic meaning can be created and attached to and around the stadium and move towards newer, desirable forms of urbanity that can in return feed back into the city itself.
This document is submitted in partial fulfilment for the degree: Masters of Urban Design, Faculty of Engineering and the Built Environment at the University of the Witwatersrand, Johannesburg, 2016
Keywords: World Cup (Soccer)--(2010: South Africa)--Economic aspects; City planning--South Africa; Stadiums--South Africa; Soccer--Tournaments--Economic aspects--South Africa